Audio and hi-fi handbook - Sinclair, Ian Robertson; Elsevier Science Publishers (Oxford ; Boston : Newnes, 1998)
Written by a team of experts and specialist contributors this comprehensive guide has proved to be an invaluable resource for professional designers and service engineers. Each chapter is written by a leading author, including Don Aldous, John Borwick, Dave Berriman and John Linsley Hood, which provides as wide a perspective as possible on high-quality sound reproduction as well as a wealth of expertise. This third edition has been fully updated to include modern valve amplifier designs, Nicam and satellite radio, and including a new section on servicing. Ian Sinclair has written over 140 books on aspects of electronics and computing and has been a regular contributor to the electronics and computing press. New chapters on valve amplifiers, in-car audio, NICAM and satellite radio, and servicing Contributors include world experts like John Linsley Hood, Nick Beer, Don Aldous, Fred Mornington-West A wide ranging guide for professionals and hobbyists alike.
Sound waves / W. Tempest -- Microphones / John Borwick -- Studio and control room acoustics / Peter Mapp -- Principles of digital audio / Allen Mornington-West -- Compact disc technology / Ken Clements -- Digital audio recording / John Watkinson -- Tape recording / John Linsley Hood -- Noise reduction systems / David Fisher -- The vinyl disc / Alvin Gold and Don Aldous -- Valve amplifiers / Morgan Jones -- Tuners and radio receivers / John Linsley Hood -- Pre-amps and inputs / John Linsley Hood -- Voltage amplifiers and controls / John Linsley Hood -- Power output stages / John Linsley Hood -- Loudspeakers / Stan Kelly -- Loudspeaker enclosures / Stan Kelly -- Headphones / Dave Berriman -- Public address and sound reinforcement / Peter Mapp -- In-car audio / Dave Berriman -- Sound synthesis / Mark Jenkins -- Interconnections / Allen Mornington-West -- NICAM stereo and satellite radio systems / Geoff Lewis -- Modern audio and Hi-Fi servicing / Nick Beer.
Rev. ed. of: Newnes audio and Hi-Fi handbook. 2nd ed. 1993.
Includes bibliographical references and index.
Keywords: High-fidelity sound systems; Electronic systems; Sound -- Equipment and supplies; Sound -- Recording and reproducing; Electronic books